Analisis Kelembagaan Agribisnis untuk Pemberdayaan Petani Gula Kelapa - Widayati, Weka; Fausayana, Ine; Nalefo, La; Muhidin, Muhidin (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2012)
Empowering farmers palm sugar is a series of systematic efforts, consistent and to achieve common goals more efficiently continuing to improve the adaptability and innovation of farmers on optimum utilization of technology within the existing institutional rules. This research aims: (1) to examines the resources potential of palm sugar farmers in agribusiness, (2) to examines the application of palm sugar technology, (3) to analyzed the institutional rules of palm sugar agribusiness. This research was conducted in the South Konawe Regency from June to November 2012. Data were collected through interviews, in-depth interview, Focus Group Discussion and observations at the location of the processing of palm sugar. Human resource potential, technology implementation, and processing of palm sugar, and institutional rules of palm sugar agribusiness analyzed qualitatively and quantitatively. The result of research showed: (1) human resources of palm sugar agribusiness at South Konawe Regency not reached the standard of sustainable business, (2) The technology to produce palm sugar is not right that the income is not optimal, and (3) institutional support palm sugar processing business has not been strong and permanent in an effort to empower entrepreneurs. So that the necessary human resource development, testing technologies, consumer preferences and business partnerships palm sugar.